Controllable Assembly and Application of Janus Smart Nanosheets for Oil Displacement - Shi, Fang; Wu, Jingchun; Zhao, Yang; Zhao, Bo; Kong, Xiangting (Frontiers in Chemistry, 2020)
Based on the development status of low permeability reservoirs, an intelligent nano-flooding agent is needed to improve the displacement efficiency of reservoirs. Janus particles have the characteristics of small size and strong interfacial activity, and the solid surfactant of Janus particles has attracted more and more attention of petroleum researchers. Janus smart nanosheets were developed by Pickering emulsion preparation. Controllable assemblies of Janus smart nanosheets were formed by adjusting the preparation ratio. The structure and properties of smart nanosheets were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy and interfacial tensiometer. The nanosheets have hydrophilic and hydrophilic properties. The particle size of silica nanoparticle is 10nm. After surface modification and high shear stress treatment, nanosheet was formed. The thickness of nanosheet dispersed in aqueous solution was 30.2nm. Experimental results show that at a given temperature, the Janus nanosheet system with low concentration can achieve ultra-low interfacial tension of 10-4mN /m, and the nanosheets have good emulsifying ability. The results provide basic insights into the bio-assembly behavior and emulsifying properties of Janus smart nanosheets, and further prove their potential for enhancing oil recovery.